Flame retardant for EVA (Ethylene Vinyl Acetate) material and preparation method of flame retardant

By using the compounding technology of organic nitrogen-based, phosphorus-based and intumescent flame retardants in EVA materials, combined with the application of modified montmorillonite, the problems of large amounts of existing flame retardants and easy precipitation are solved, and EVA is realized Efficient flame retardancy and maintenance of mechanical properties of the material.

CN119350718AActive Publication Date: 2025-01-24DONGGUAN HONGTAIJI FLAME RETARDANT MATERIAL CO LTD

Patent Information

Application Number
CN202411643827.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-24
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The existing flame retardant is added in large amounts and easy to precipitate in EVA materials, which reduces the flame retardancy and mechanical properties of the materials.

Method used

The compound technology of organic nitrogen-based flame retardants, phosphorus-based flame retardants and intumescent flame retardants is used, combined with the use of modified montmorillonite, to form a synergistic effect, improve the flame retardant performance and reduce the amount of addition.

Benefits of technology

The good flame retardancy and flame retardant stability of EVA materials are achieved with a small amount of use, while avoiding the impact on the mechanical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005139181850000051
    Figure BDA0005139181850000051
  • Figure BDA0005139181850000061
    Figure BDA0005139181850000061
  • Figure BDA0005139181850000071
    Figure BDA0005139181850000071
Patent Text Reader

Abstract

The invention relates to the field of flame retardants, and particularly discloses a flame retardant for an EVA material and a preparation method of the flame retardant. The invention relates to a flame retardant for an EVA material. The flame retardant is prepared from the following raw materials in percentage by weight: 30-40% of an organic nitrogen flame retardant, 45-55% of a phosphorus flame retardant, 10-15% of an intumescent flame retardant and the balance of modified montmorillonite, the modified montmorillonite is prepared from montmorillonite, methacryloyloxyethyl trimethyl ammonium chloride, a polymethyl vinyl ether / maleic anhydride copolymer, a silane coupling agent, a dispersing agent and an activating agent; the preparation method comprises the following steps: grinding the organic nitrogen flame retardant, the phosphorus flame retardant and the intumescent flame retardant, and stirring and dispersing with the modified montmorillonite; the preparation process is simple, the usage amount of the prepared flame retardant in the EVA material is small, and the flame retardant has good flame-retardant stability and does not affect the mechanical property of the EVA material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of flame retardants, and more specifically, to a flame retardant for EVA materials and a preparation method thereof. Background Art

[0002] EVA material, full name Ethylene-Vinyl Acetate Copolymer, is a thermoplastic made by copolymerizing ethylene monomer and vinyl acetate monomer. EVA material has the advantages of good elasticity, softness, tear resistance and corrosion resistance, and is widely used in sealing materials, cable materials and other fields.

[0003] However, the flame retardant properties of EVA materials are poor, and flame retardants are generally added to improve the flame retardant properties of EVA materials. Commonly used environmentally friendly flame retardants include inorganic flame retardants, phosphorus flame retardants, organic nitrogen flame retardants and phosphorus nitrogen flame retardants, but inorganic flame retardants generally include magnesium hydroxide, etc., and the usage amount generally reaches 40-60%, and the addition amount of phosphorus flame retardants is generally 20-30%. The addition amount of flame retardants is large, which is easy to affect the mechanical properties of EVA materials; while organic nitrogen flame retardants and phosphorus nitrogen flame retardants are generally hygroscopic. When added to EVA materials, as EVA materials are used, organic nitrogen flame retardants will migrate or precipitate from EVA materials, reducing the flame retardancy of EVA materials. Summary of the invention

[0004] In order to solve the problem that conventional flame retardants are used in EVA materials, the amount of addition is large and they are easy to precipitate, thereby reducing the flame retardancy and mechanical properties of the EVA material, the present application provides a flame retardant for EVA materials and a preparation method thereof.

[0005] In the first aspect, the present application provides a flame retardant for EVA material, which adopts the following technical solution: A flame retardant for EVA material, prepared from the following raw materials in percentage by weight: Organic nitrogen flame retardant 30-40% Phosphorus flame retardant 45-55% Intumescent flame retardant 10-15% Modified montmorillonite residue; The modified montmorillonite is prepared from montmorillonite, methacryloyloxyethyl trimethyl ammonium chloride, polymethyl vinyl ether / maleic anhydride copolymer, silane coupling agent, dispersant and activator.

[0006] By adopting the above technical scheme, organic nitrogen flame retardants can generate non-combustible gas to dilute the concentration of combustible gas, and the generated carbon layer has the effect of heat insulation and oxygen isolation. Phosphorus flame retardants decompose at high temperature to produce phosphoric acid, which further promotes the formation of carbon layer and enhances the stability and integrity of carbon layer. Intumescent flame retardants expand rapidly when heated to form a dense foam-like carbon layer, which can not only isolate oxygen and heat, but also effectively prevent the spread of flames. Organic nitrogen flame retardants, phosphorus flame retardants and intumescent flame retardants have good synergistic effects and achieve good flame retardant effects with less dosage. Modified montmorillonite can be evenly dispersed in the flame retardant system and form a uniform hydrophobic protective layer on the surface of the flame retardant, which improves the stability of the flame retardant and plays a good flame retardant synergistic role, further reducing the amount of flame retardant, thereby maintaining a good flame retardant effect while avoiding the influence on the mechanical properties of EVA materials.

[0007] Preferably, the modified montmorillonite is prepared from the following raw materials in parts by weight: Montmorillonite 100-120 parts 100-200 parts of 55-85wt% ethanol aqueous solution Silane coupling agent 5-10 parts 2-4 parts of activator Dispersant 2-4 parts Methacryloyloxyethyl trimethyl ammonium chloride 5-10 parts 4-6 parts of polymethyl vinyl ether / maleic anhydride copolymer.

[0008] By adopting the above technical scheme, the dispersant and the activator can improve the surface modification efficiency of montmorillonite, silane coupling agent, methacryloyloxyethyl trimethyl ammonium chloride and polymethyl vinyl ether / maleic anhydride copolymer. The silane coupling agent, methacryloyloxyethyl trimethyl ammonium chloride and polymethyl vinyl ether / maleic anhydride copolymer can form a cross-linked network structure on the surface of montmorillonite, increase the interlayer spacing of montmorillonite, improve the dispersion performance of montmorillonite in the flame retardant system, and improve the compatibility of montmorillonite in organic matter. A uniform hydrophobic layer is formed on the surface of the flame retardant, so that the flame retardant has better flame retardant stability while reducing the influence of the addition of the flame retardant on the mechanical properties of the EVA material.

[0009] Preferably, the activator is composed of ammonium persulfate and ethylenediamine in a weight ratio of 1:(0.2-0.4).

[0010] By adopting the above technical solution, ammonium persulfate and ethylenediamine in an optimal weight ratio are used as activators, which can improve the modification efficiency of montmorillonite and thus improve the flame retardant stability of the prepared flame retardant.

[0011] Preferably, the dispersant is any one or a combination of alkyl aryl phosphates, alkyl benzene sulfonates, and dialkyl sulfosuccinates.

[0012] By adopting the above technical solution, the above dispersant can cooperate with the activator to improve the dispersibility of montmorillonite, thereby improving the modification efficiency of the modified montmorillonite.

[0013] Preferably, the silane coupling agent is composed of tetramethyldivinyldisilazane and dodecyltriethoxysilane in a weight ratio of 1:(1-3).

[0014] By adopting the above technical scheme, the silane coupling agent composed of tetramethyldivinyldisilazane and dodecyltriethoxysilane can form an interwoven system of silanes, thereby improving the dispersibility and hydrophobicity of the modified montmorillonite obtained, and improving the compatibility of montmorillonite with EVA materials, so that when the flame retardant is applied to the EVA material, it can have better flame retardancy with a smaller addition amount.

[0015] Preferably, the modified montmorillonite is prepared by the following steps: Add the dispersant and activator to the ethanol aqueous solution, stir and dissolve, then add montmorillonite, silane coupling agent, methacryloyloxyethyl trimethyl ammonium chloride and polymethyl vinyl ether / maleic anhydride copolymer, heat to 60-70°C, react for 2-3h, filter and dry to obtain modified montmorillonite.

[0016] By adopting the above technical scheme, in the preparation process of modified montmorillonite, the addition of dispersant and activator can effectively improve the dispersibility of montmorillonite in ethanol aqueous solution, ensuring that the components are fully mixed. Silane coupling agent, methacryloyloxyethyl trimethyl ammonium chloride and polymethyl vinyl ether / maleic anhydride copolymer are added later to form a cross-linked hydrophobic protective layer on the surface of montmorillonite. The modified montmorillonite prepared by this process can significantly reduce the amount of flame retardant added, and improve the flame retardant properties of EVA materials without affecting the mechanical properties of EVA materials.

[0017] Preferably, the organic nitrogen flame retardant is melamine cyanurate and / or melamine phosphate.

[0018] Preferably, the phosphorus-based flame retardant is one or a combination of diethyl aluminum hypophosphite, boron phosphate, ammonium polyphosphate and ammonium phosphate.

[0019] Preferably, the intumescent flame retardant is piperazine pyrophosphate.

[0020] By adopting the above technical scheme, melamine cyanurate and / or melamine phosphate are selected as organic nitrogen flame retardants, one or a combination of diethyl aluminum hypophosphite, boron phosphate, ammonium polyphosphate and ammonium phosphate are selected as phosphorus flame retardants, and piperazine pyrophosphate is used as an intumescent flame retardant. The three have a good synergistic effect. When combustion occurs, the phosphorus flame retardant and the organic nitrogen flame retardant can form a carbon layer, and under the action of the intumescent carbon layer of the intumescent flame retardant, the contact between the partition material and the air is cut off, which plays a role of rapid flame retardancy; at the same time, a large amount of inert gas is released during the combustion process to dilute the concentration of combustible gas and inhibit the spread of flame. The combined use of the three can greatly reduce the amount of flame retardant used.

[0021] In a second aspect, the present application provides a method for preparing a flame retardant for EVA material, using the following technical solution: A method for preparing a flame retardant for EVA material, comprising the following steps: S1. First, the phosphorus flame retardant, the organic nitrogen flame retardant and the intumescent flame retardant are crushed to a particle size of less than 5 μm; S2. Evenly disperse and stir the phosphorus flame retardant, the organic nitrogen flame retardant, the intumescent flame retardant and the modified montmorillonite to prepare a flame retardant for EVA material.

[0022] By adopting the above technical solution, the phosphorus flame retardant, the organic nitrogen flame retardant and the intumescent flame retardant are crushed to a particle size of less than 5 μm respectively, and then fully mixed with the modified montmorillonite to ensure that each component is evenly dispersed, thereby improving the uniform dispersion performance of the flame retardant.

[0023] In summary, this application has the following beneficial effects: 1. The flame retardant for EVA material of the present application is compounded by an organic nitrogen flame retardant, a phosphorus flame retardant and an intumescent flame retardant in a preferred weight ratio. The modified montmorillonite is prepared by montmorillonite, methacryloyloxyethyl trimethylammonium chloride, polymethyl vinyl ether / maleic anhydride copolymer, a silane coupling agent, a dispersant and an activator. The modified montmorillonite can be evenly dispersed in the flame retardant system and form a uniform hydrophobic protective layer on the surface of the flame retardant. Under the synergistic effect of the modified montmorillonite, while improving the flame retardancy and flame retardant stability of the flame retardant, it plays a good flame retardant synergistic role, further reducing the amount of flame retardant, thereby maintaining a good flame retardant effect while not affecting the mechanical properties of the EVA material.

[0024] 2. By using ammonium persulfate and ethylenediamine in a better weight ratio as activators, and tetramethyldivinyldisilazane and dodecyltriethoxysilane as silane coupling agents, the compatibility of montmorillonite and EVA materials is improved, so that when the flame retardant is used in the EVA material, it can have better flame retardancy with a smaller addition amount.

[0025] 3. When the flame retardant of the present application is applied to EVA material, it can have good flame retardancy and flame retardant stability at a relatively small dosage, and will not affect the mechanical properties of the EVA material. DETAILED DESCRIPTION

[0026] The present application is further described in detail below with reference to the embodiments.

[0027] The following are the sources and specifications of some raw materials of this application. The raw materials used in the preparation examples and embodiments of this application can be obtained from the market, including but not limited to the raw materials of the following models and manufacturers. Raw materials with equivalent performance can be used: 1. Montmorillonite: Lingshou, 325 mesh, whiteness 90%, content 92%, density 2.63g / cm 3 ; 2. Polymethyl vinyl ether / maleic anhydride copolymer: Chengfeng, CAS No. 9011-16-9, content 98%; 3. Melamine cyanurate: Taixing HT-211, content 99.8%; 4. Ammonium polyphosphate: CAS No. 68333-79-9; 5. Piperazine pyrophosphate: CAS No. 66034-17-1, phosphorus content 20-22%, nitrogen content 23-25%; 6. Diethylaluminum hypophosphite: CAS225789-38-8, content 99%; 7. EVA material: Formosa Plastics 7470M.

[0028] Preparation example of modified montmorillonite Preparation Example 1 Preparation Example 1 discloses a modified montmorillonite, which is prepared by the following steps: 0.2kg of sodium dodecylbenzenesulfonate as a dispersant and 0.2kg of ammonium persulfate as an activator are added to 10kg of 55wt% ethanol aqueous solution, and after stirring and dissolving, 10kg of montmorillonite, 1kg of silane coupling agent (composed of 0.5kg of vinyltrimethoxysilane and 0.5kg of dodecyltriethoxysilane), 0.5kg of methacryloyloxyethyltrimethylammonium chloride and 0.6kg of polymethylvinyl ether / maleic anhydride copolymer are added, the temperature is raised to 60°C, the reaction is carried out for 2h, the mixture is filtered, dried and dispersed, and the modified montmorillonite is prepared.

[0029] Preparation Example 2-3 The difference between Preparation Example 2-3 and Preparation Example 1 is that the amount of raw materials used and the preparation conditions are different, see Table 1 below for details.

[0030] Table 1 Parameters of Preparation Examples 1-3 Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that the activator is different. The activator of Preparation Example 4 is composed of ammonium persulfate and ethylenediamine in a weight ratio of 1:0.2, and the rest is the same as Preparation Example 1.

[0031] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 1 is that the activator in Preparation Example 5 is composed of ammonium persulfate and ethylenediamine in a weight ratio of 1:0.4, and the rest is the same as Preparation Example 1.

[0032] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 4 is that the silane coupling agent is different. The silane coupling agent in Preparation Example 6 is composed of tetramethyldivinyldisilazane and dodecyltriethoxysilane in a weight ratio of 1:1, and the rest is the same as Preparation Example 4.

[0033] Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 4 is that the silane coupling agent in Preparation Example 7 is composed of tetramethyldivinyldisilazane and dodecyltriethoxysilane in a weight ratio of 1:3, and the rest is the same as Preparation Example 4.

[0034] Preparation Comparative Example 1 The difference between Preparation Comparative Example 1 and Preparation Example 6 is that an equal amount of methacryloyloxyethyltrimethylammonium chloride is replaced by polydimethyldiallylammonium chloride, and the rest is the same as Preparation Example 6.

[0035] Preparation Comparative Example 2 The difference between Preparation Comparative Example 2 and Preparation Example 6 is that the polymethyl vinyl ether / maleic anhydride copolymer is replaced with methacryloyloxyethyl trimethyl ammonium chloride in equal amounts, and the rest is the same as Preparation Example 6. Example

[0036] Example 1 Example 1 discloses a flame retardant for EVA material, which is prepared by the following steps: S1. First, a phosphorus flame retardant (composed of diethyl aluminum hypophosphite and ammonium phosphate in a weight ratio of 2:1), melamine cyanurate as an organic nitrogen flame retardant, and piperazine pyrophosphate as an intumescent flame retardant are crushed to a particle size of less than 5 μm; S2. 4.5 kg of crushed phosphorus-based flame retardant, 4 kg of organic nitrogen-based flame retardant, 1.2 kg of intumescent flame retardant and 0.3 kg of modified montmorillonite obtained in Preparation Example 1 were dispersed at a mixing rate of 2500 r / min for 60 min to obtain a flame retardant for EVA material.

[0037] Example 2-3 The difference between Example 2-3 and Example 1 is that the amount of raw materials used and the preparation conditions are different, see Table 2 below for details.

[0038] Table 2 Parameters of Examples 1-3 Embodiment 4-7 The difference between Examples 4-7 and Example 1 is that the sources of the modified montmorillonite are different, see Table 3 below for details.

[0039] Table 3 Sources of modified montmorillonite of Examples 4-7 Example Sources of modified montmorillonite Example 4 Preparation Example 4 Example 5 Preparation Example 5 Example 6 Preparation Example 6 Example 7 Preparation Example 7 Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 6 is that the modified montmorillonite is derived from the preparation of Comparative Example 1, and the rest is the same as Example 6.

[0040] Comparative Example 2 The difference between Comparative Example 2 and Example 6 is that the modified montmorillonite is derived from the preparation of Comparative Example 2, and the rest is the same as Example 6.

[0041] Comparative Example 3 The difference between Comparative Example 3 and Example 6 is that the modified montmorillonite is replaced by montmorillonite in an equal amount, and the rest is the same as Example 6.

[0042] Comparative Example 4 The difference between Comparative Example 4 and Example 6 is that the amount of the intumescent flame retardant used is 0.5 kg, the amount of the organic nitrogen flame retardant used is 4.7 kg, and the rest is the same as Example 6.

[0043] Application Examples Application Example 1 Application Example 1 discloses an EVA material, and the preparation process is as follows: 9 kg of EVA resin and 1 kg of the flame retardant prepared in Example 1 were uniformly mixed and melt-extruded to prepare an EVA material.

[0044] Application Example 2-11 The difference between Application Example 2-11 and Application Example 1 is that the source of the flame retardant is different, see Table 4 below for details.

[0045] Table 4 Sources of flame retardants in application examples 2-11 Application Examples Sources of flame retardants Application Example 2 Example 2 Application Example 3 Example 3 Application Example 4 Example 4 Application Example 5 Example 5 Application Example 6 Example 6 Application Example 7 Example 7 Application Example 8 Comparative Example 1 Application Example 9 Comparative Example 2 Application Example 10 Comparative Example 3 Application Example 11 Comparative Example 4 Performance test The EVA material prepared in the following corresponding example 1-11 was subjected to performance test: The EVA material prepared in the application example 1-12 was injection molded, cut into test strips with a thickness of 1.5 mm and a width of 50 mm, and the performance test was performed; 1. Breaking strength test: Use a tensile testing machine to test the breaking strength (MPa) of the test strips, test and record the test results; 2. Flame retardancy test: According to the test method in GB / T 2406, the test strip is subjected to a limiting oxygen index test, which is recorded as the first limiting oxygen index (unit: %), and the test results are recorded; 3. Flame retardant stability test: The test strip is subjected to a limiting oxygen index test, recorded as the second limiting oxygen index (unit: %), and the test results are tested and recorded; the following is the performance test data of the EVA material prepared in Application Examples 1-11, see Table 5 below for details.

[0046] Table 5 Performance data of EVA materials of application examples 1-11 Combining Application Examples 1-3 and Application Examples 4-5 and Table 5, it can be concluded that the flame retardant prepared by using ammonium persulfate and ethylenediamine in a preferred weight ratio as activators is applied to EVA materials and has good flame retardancy and mechanical properties. Compared with Application Example 1, Application Example 4-5 has an increased breaking strength of 12MPa and an increased first limiting oxygen index of 0.9%. After the flame retardant stability test, the second limiting oxygen index of Application Example 1 is reduced by 0.9%, while the second limiting oxygen index of Application Example 4 is reduced by 0.6%. Compared with Application Example 1, Application Example 4 has improved flame retardant stability.

[0047] Combining Application Example 4 and Application Examples 6-7 and Table 5, it can be concluded that the flame retardant prepared by using tetramethyldivinyldisilazane and dodecyltriethoxysilane in a preferred weight ratio as a silane coupling agent is applied to EVA materials and has good flame retardancy and mechanical properties. Compared with Application Example 4, Application Examples 6-7 have an increase in breaking strength of 10MPa, an increase in the first limiting oxygen index of 0.9%, and a decrease in the second limiting oxygen index of Application Example 6 of 0.2%. Compared with Application Example 4, Application Example 6 has an improved flame retardant stability.

[0048] Further combined with Application Examples 6 and Application Examples 8-10 and Table 5, it can be concluded that the modified montmorillonite prepared by using the dispersant, activator, silane coupling agent, methacryloyloxyethyl trimethyl ammonium chloride and polymethyl vinyl ether / maleic anhydride copolymer of the present application, the prepared flame retardant is applied to EVA materials, and has good flame retardancy, flame retardant stability and mechanical properties. In Application Examples 8-9, the components of methacryloyloxyethyl trimethyl ammonium chloride and polymethyl vinyl ether / maleic anhydride copolymer are changed, and the breaking strength is reduced by 33MPa, the first limiting oxygen index is reduced by 3.5%, and the flame retardant stability is also significantly reduced; in Application Example 10, montmorillonite is directly used, and the prepared flame retardant is applied to EVA materials, and the flame retardancy, flame retardant stability and mechanical properties are significantly reduced, which may be because the modified montmorillonite reduces the dispersion and hydrophobic protection of the flame retardant system, thereby reducing the flame retardancy and mechanical properties of the EVA material.

[0049] Combining Application Example 6 and Application Example 11 with Table 5, it can be concluded that optimizing the ratio of organic nitrogen flame retardant, phosphorus flame retardant and intumescent flame retardant can improve the flame retardancy and flame retardant stability of the prepared flame retardant.

[0050] In summary, the amount of the flame retardant of the present application used in the EVA material is relatively small, 10% can achieve a limiting oxygen index of 34%, and will not affect the mechanical properties of the EVA material.

[0051] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A flame retardant for EVA material, characterized in that: Made from the following raw materials in weight percentage: Organic nitrogen flame retardant 30-40% Phosphorus flame retardant 45-55% Intumescent flame retardant 10-15% Modified montmorillonite residue; The modified montmorillonite is prepared from montmorillonite, methacryloyloxyethyl trimethyl ammonium chloride, polymethyl vinyl ether / maleic anhydride copolymer, silane coupling agent, dispersant and activator.

2. The flame retardant for EVA material according to claim 1, characterized in that: The modified montmorillonite is prepared from the following raw materials in parts by weight: Montmorillonite 100-120 parts 100-200 parts of 55-85wt% ethanol aqueous solution Silane coupling agent 5-10 parts 2-4 parts of activator Dispersant 2-4 parts Methacryloyloxyethyl trimethyl ammonium chloride 5-10 parts 4-6 parts of polymethyl vinyl ether / maleic anhydride copolymer.

3. A flame retardant for EVA material according to claim 2, characterized in that: The activator is composed of ammonium persulfate and ethylenediamine in a weight ratio of 1:(0.2-0.4).

4. The flame retardant for EVA material according to claim 2, characterized in that: The dispersant is any one or a combination of alkyl aryl phosphate, alkyl benzene sulfonate, and dialkyl sulfosuccinate.

5. The flame retardant for EVA material according to claim 2, characterized in that: The silane coupling agent is composed of tetramethyldivinyldisilazane and dodecyltriethoxysilane in a weight ratio of 1:(1-3).

6. A flame retardant for EVA material according to any one of claims 2 to 5, characterized in that: The modified montmorillonite is prepared by the following steps: Add the dispersant and activator to the ethanol aqueous solution, stir and dissolve, then add montmorillonite, silane coupling agent, methacryloyloxyethyl trimethyl ammonium chloride and polymethyl vinyl ether / maleic anhydride copolymer, heat to 60-70°C, react for 2-3h, filter and dry to obtain modified montmorillonite.

7. The flame retardant for EVA material according to claim 1, characterized in that: The organic nitrogen flame retardant is melamine cyanurate and / or melamine phosphate.

8. The flame retardant for EVA material according to claim 1, characterized in that: The phosphorus-based flame retardant is one or a combination of diethyl aluminum hypophosphite, boron phosphate, ammonium polyphosphate and ammonium phosphate.

9. The flame retardant for EVA material according to claim 1, characterized in that: The intumescent flame retardant is piperazine pyrophosphate.

10. A method for preparing a flame retardant for EVA material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Firstly, the phosphorus flame retardant, the organic nitrogen flame retardant and the intumescent flame retardant are crushed to a particle size of less than 5µm; S2. Evenly disperse and stir the phosphorus flame retardant, the organic nitrogen flame retardant, the intumescent flame retardant and the modified montmorillonite to prepare a flame retardant for EVA material.

Citation Information

Patent Citations

  • Phosphorus nitrogen series expansion type anti-flaming nano composite material with high thermal stability

    CN101168607A

  • Halogen-free expanded flame-retardant polypropylene film

    CN101831109A

  • Method for modifying attapulgite and attapulgite composite material

    CN113831764A

  • Flame retardant for TPU charging pile and preparation method thereof

    CN118852732A

  • Triazine-based highly-effective intumescent flame retardant and intumescent flame retardant polypropylene

    WO2017096519A1

Cited By

  • Modified magnesium hydroxide for high filling material and preparation method of modified magnesium hydroxide

    CN120118539A

  • Flame-retardant TPU (thermoplastic polyurethane) film and trimming treatment equipment

    CN121340757A